One new genus and species of the tribe Meconematini (Orthoptera, Tettigoniidae) from Sichuan, China with description of the male sex and transfer of Acosmetura carinata Liu, Zhou & Bi, 2008 to the new genus - Ming, Shi Fu; Xun, Bian (Zootaxa, 2013)
The paper deals with a new genus, a new species and a new combination, i. e. Sinocyrtaspiodea gen. nov., Sinocyrtaspiodea longicercus sp. nov. and Sinocyrtaspiodea carinata (Liu, Zhou & Bi, 2008) com. nov. All specimens are deposited in the Museum of Hebei University.